Improving Public Service Quality through the Development of Online Service Innovations in Public Sector Organizations in Indonesia - Tetet Cahyati (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to explore the potential of online service innovations in the public sector in Indonesia to improve the quality of public services. The study employs a mixed-methods approach, including surveys, interviews, and case studies, to gather data from various public sector organizations in Indonesia. The results indicate that the development of online service innovations has the potential to improve the quality of public services, particularly in terms of accessibility, efficiency, and effectiveness. The study also identifies several challenges in implementing online service innovations, including technical issues, limited resources, and resistance to change. The findings suggest that public sector organizations in Indonesia should prioritize the development of online service innovations as part of their efforts to improve the quality of public services. This research provides valuable insights for policymakers and practitioners who are interested in enhancing public service delivery through the use of technology.